(untitled) (Journal of Contemporary Philology, 2019)
The aim of this study is to evaluate the results of the laboratory and classroom-based research studies that investigate the effect of pronunciation instruction. The analysis shows that pronunciation instruction facilitates modification of learners’ L2 pronunciation. Different types of instruction develop different aspects of pronunciation as a language skill; in particular, prosody-focused instruction considerably improves learners’ communicative performance. Inaddition, the corrective feedback given by the teacher is of great significance for enhancing learners’ noticing skills and raising their phonological awareness and critical attitude towards their own pronunciation. The effectiveness of phonetic instruction suggests that there are long-term benefits of pronunciation training if it is systematically incorporated into the teaching practice.